2014
DOI: 10.1016/j.virol.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Cellular DDX3 regulates Japanese encephalitis virus replication by interacting with viral un-translated regions

Abstract: Japanese encephalitis virus is one of the most common causes for epidemic viral encephalitis in humans and animals. Herein we demonstrated that cellular helicase DDX3 is involved in JEV replication. DDX3 knockdown inhibits JEV replication. The helicase activity of DDX3 is crucial for JEV replication. GST-pulldown and co-immunoprecipitation experiments demonstrated that DDX3 could interact with JEV non-structural proteins 3 and 5. Co-immunoprecipitation and confocal microscopy analysis confirmed that DDX3 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 78 publications
0
75
0
Order By: Relevance
“…Cell proteins binding to the genome 3′ NCR and/or to a viral replication complex protein may function to facilitate the initiation of minus strand viral RNA synthesis. A number of different cell proteins have been reported to bind to a 3′ NCR flavivirus probe including La, PTB, PABP, NF-9 FBP1, DDX5, eEF1A, TIAR/TIA-1 (De Nova-Ocampo, Villegas-Sepulveda et al 2002, Polacek, Friebe et al 2009, Chien, Liao et al 2011, Gomila, Martin et al 2011, Li, Ge et al 2013, Albornoz, Carletti et al 2014) but the region of the 3′ NCR to which these proteins bound was not mapped and some of these proteins also bound to additional flavivirus RNA terminal sequences (De Nova-Ocampo, Villegas-Sepulveda et al 2002, Yocupicio-Monroy, Padmanabhan et al 2007, Li, Ge et al 2014) as well as to some of the viral proteins (Li, Ge et al 2013, Li, Ge et al 2014). Additional studies identified cell proteins binding to particular regions within the flavivirus 3′ NCR.…”
Section: Cell Protein Involvement In Unpairing Of the Stem At The mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell proteins binding to the genome 3′ NCR and/or to a viral replication complex protein may function to facilitate the initiation of minus strand viral RNA synthesis. A number of different cell proteins have been reported to bind to a 3′ NCR flavivirus probe including La, PTB, PABP, NF-9 FBP1, DDX5, eEF1A, TIAR/TIA-1 (De Nova-Ocampo, Villegas-Sepulveda et al 2002, Polacek, Friebe et al 2009, Chien, Liao et al 2011, Gomila, Martin et al 2011, Li, Ge et al 2013, Albornoz, Carletti et al 2014) but the region of the 3′ NCR to which these proteins bound was not mapped and some of these proteins also bound to additional flavivirus RNA terminal sequences (De Nova-Ocampo, Villegas-Sepulveda et al 2002, Yocupicio-Monroy, Padmanabhan et al 2007, Li, Ge et al 2014) as well as to some of the viral proteins (Li, Ge et al 2013, Li, Ge et al 2014). Additional studies identified cell proteins binding to particular regions within the flavivirus 3′ NCR.…”
Section: Cell Protein Involvement In Unpairing Of the Stem At The mentioning
confidence: 99%
“…Both DDX5 and DDX3 have been reported to bind to both the 3′ NCR and the 5′ NCR and to positively regulate genome translation (Li, Ge et al 2014). Poly(A) binding protein (PABP) binds to an unmapped region of the 3′ NCR located 5′ of the dumbbell RNA structures and facilitates in vitro translation (Polacek, Friebe et al 2009).…”
Section: Cell Protein Involvement In Viral Rna Translationmentioning
confidence: 99%
“…Evidence suggests that DDX3 is a host factor coopted by multiple viruses, including HIV and hepatitis C virus (HCV) (19)(20)(21)(22)(23). One report showed that DDX3 facilitates the Rev/Rev-responsive element (RRE)-mediated nuclear export of HIV genomic RNA (21); others then showed that DDX3 promotes HIV-1 genomic RNA translation (23).…”
Section: Upon Entry Into Host Cells Viruses Encounter Host Factors Tmentioning
confidence: 99%
“…Recent studies have revealed that the cellular ATPase/RNA helicase X-linked DEAD-box polypeptide 3 (DDX3) is an essential host factor for the replication of viruses belonging to different families: CMV (13) (Herpesviridae), HIV-1 (14) (Retroviridae), HCV (15)(16)(17)(18), Japanese Encephalitis virus (19), Dengue virus (DENV) (20), West Nile virus (WNV; Flaviviridae) (21), Vaccinia virus (22-24) (Poxviridae), and Norovirus (25) (Caliciviridae). The exact mechanisms of interaction of this protein with individual pathogens are still poorly understood (26).…”
mentioning
confidence: 99%